2020
DOI: 10.1186/s12284-020-00418-z
|View full text |Cite
|
Sign up to set email alerts
|

UvAtg8-Mediated Autophagy Regulates Fungal Growth, Stress Responses, Conidiation, and Pathogenesis in Ustilaginoidea virens

Abstract: Background: Ustilaginoidea virens has become one of the most devastating rice pathogens in China, as well as other rice-growing areas. Autophagy is an important process in normal cell differentiation and development among various organisms. To date, there has been no optimized experimental system introduced for the study of autophagy in U. virens. In addition, the function of autophagy in pathogenesis remains unknown in U. virens. Therefore, the functional analyses of UvAtg8 may potentially shed some light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…This led to the functional identification of various pathogenic genes in U. virens, including iUvt3277, UvCom1, UvPRO1, UvAc1, UvPdeH, SCRE1, SCRE2 (UV_1261), UvBI-1, UvPmk1, UvCDC2, UvCdc3, UvCdc10, UvCdc11, UvCdc12, UvPal1, UvHox2, UvRpd3, UvSlt2, UvATG8, UvZnFTF1, UvMSN2, UvCGBP1, and UvEC1. These genes play important roles in the hyphal growth, conidiation, stress responses, and virulence of U. virens [46][47][48][49][50][51][52][53][54][55]. In the current study, we identified and functionally characterized CCHC-type zinc-finger proteins in U. virens.…”
Section: Discussionmentioning
confidence: 95%
“…This led to the functional identification of various pathogenic genes in U. virens, including iUvt3277, UvCom1, UvPRO1, UvAc1, UvPdeH, SCRE1, SCRE2 (UV_1261), UvBI-1, UvPmk1, UvCDC2, UvCdc3, UvCdc10, UvCdc11, UvCdc12, UvPal1, UvHox2, UvRpd3, UvSlt2, UvATG8, UvZnFTF1, UvMSN2, UvCGBP1, and UvEC1. These genes play important roles in the hyphal growth, conidiation, stress responses, and virulence of U. virens [46][47][48][49][50][51][52][53][54][55]. In the current study, we identified and functionally characterized CCHC-type zinc-finger proteins in U. virens.…”
Section: Discussionmentioning
confidence: 95%
“…The cellular morphogenetic protein UvPal1 affects hyphal growth, cell morphology, stress adaptation and virulence, and UvPal1 physically interacts with the cell division control protein UvCdc11 (also called septin) to mediate the formation of the septin complex to maintain cellular morphology and virulence [ 12 ]. Autophagy 8 (UvAtg8)-mediated autophagy plays important roles in growth, stress responses, production of toxic compounds, conidiation, secondary spore formation and pathogenicity in U. virens [ 37 ]. The histone deacetylase UvRpd3 and the mitogen-activated protein kinase (MAPK) UvSlt2 affect U. virens virulence , and both proteins interact to remove 2-hydroxyisobutyrylation and acetylation marks from UvSlt2 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 1010 bp upstream and 996 bp downstream flanking sequences of Uvsun1 were amplified with primer pairs of S1F/S1R and S2F/S2R, respectively, and fused with the 1396 bp hygromycin-resistance cassette ( Hph ) (amplified with primers: HF and HR) from pSK1044 ( Yu et al, 2015 ) by ClonExpress TM MultiS One Step Cloning Kit (Vazyme) to the pMD19-T vector (Takara). Protoplast preparation and recovery of hygromycin-resistant transformants were performed as described previously ( Guo et al, 2019 ; Meng et al, 2020 ). For complementation, a fragment containing the entire Uvsun1 gene and its native promoter region (upstream 1.5 kb sequence) were amplified with primer pairs of pKO1-SC1F/pKO1-SC1R.…”
Section: Methodsmentioning
confidence: 99%
“…Step Cloning Kit (Vazyme) to the pMD19-T vector (Takara). Protoplast preparation and recovery of hygromycin-resistant transformants were performed as described previously (Guo et al, 2019;Meng et al, 2020). For complementation, a fragment containing the entire Uvsun1 gene and its native promoter region (upstream 1.5 kb sequence) were amplified with primer pairs of pKO1-SC1F/ pKO1-SC1R.…”
Section: Multis Onementioning
confidence: 99%
See 1 more Smart Citation